'From God' or 'from Heaven'?: ex ýpsus in Luke 1,78 - Lanier, Gregory R. (Biblica, 2016)
The phrase ἀνατολὴ ἐξ ὕψους in Luke 1,78 has long proven enigmatic. This note focuses on the meaning of ἐξ ὕψους. Scholars have debated whether it should be interpreted as 'from God/Most High' or 'from upon high/heaven'. The use of ὕψιστος elsewhere in Luke 1-2 appears to be impacting the reading of 1,78 unnecessarily. An analysis of ~280 instances of ὕψος and ~230 of ὕψιστος in the relevant Jewish/christian sources suggests that while ὕψιστος often refers to God, ὕψος never does. The ἀνατολή should be understood as coming 'from heaven', thus impacting one’s reading of this metaphor in the Benedictus.